A Qualitative Exploration of Chinese Self-Love - Xue, Li Ming; Huang, Xi Ting; Wu, Na; Yue, Tong (Frontiers in Psychology, 2021)
Although self-love is an important topic, it has not been viewed as appropriate for psychological research, especially in China. We conducted two studies to understand how Chinese people view self-love. In the first study, we surveyed 109 Chinese people about the dimensions of self-love using an open-ended questionnaire. In the second study, 18 participants were selected by means of intensity sampling and interviewed about the connotations and structure of Chinese self-love. The two studies revealed three important aspects of the Chinese understanding of self-love: (1) self-love has four dimensions: self, family, others, and society; (2) it comprises five components: self-cherishing, self-acceptance, self-restraint, self-responsibility, and self-persistence; and (3) the five components of self-love are linked together to form a stable personality structure. The reliability and validity of the two studies were strong. Finally, the results showed that Chinese self-love is dominated by Confucian culture, which provides guiding principles for how to be human. At the same time, it shows that there are differences in the understanding of self-love between Chinese and Western cultures, which provides an empirical basis for further research based on cross-cultural psychology and self-love psychology.